Exploring Students’ Perspectives on Using AI in English Speaking Education with Metaphorical Expressions - Han, Yi; Nazifah, Hamidun; Rozilawati, Mahadi (Journal of Communication in Scientific Inquiry (JCSI), 2025)
This qualitative study explores university students’ perceptions of using artificial intelligence (AI) in their English-speaking learning through metaphor analysis. As AI becomes more integrated into language education, understanding how students conceptualize its role offers valuable insights for designing effective AI-assisted learning environments. The research examines 244 metaphorical expressions provided by English as a Foreign Language (EFL) students from various majors at a public university in mainland China. Students completed open-ended survey question to express their metaphorical representations of AI in their language learning journey. The responses were systematically categorized and analyzed, revealing a variety of positive and negative attitudes. Positive metaphors included concepts such as “enhanced practice opportunities,” “language learning facilitator,” “future necessity,” and “personalized assistance,” highlighting AI’s potential to support individualized learning, provide meaningful practice, and aid in mastering spoken English. Conversely, negative metaphors like “complexity” and “over-reliance” pointed to concerns about navigating AI tools and the risk of excessive dependence on technology. These metaphorical insights shed light on students’ underlying beliefs about AI and its role in developing English-speaking skills. Understanding these perceptions is crucial for educators and curriculum designers to ensure AI tools are integrated in ways that enhance student engagement, improve speaking proficiency, and address potential challenges. Kajian kualitatif ini meneroka persepsi pelajar universiti terhadap penggunaan kecerdasan buatan (AI) dalam pembelajaran bertutur bahasa Inggeris melalui analisis metafora. Seramai 244 pelajar Bahasa Inggeris sebagai Bahasa Asing (EFL) dari pelbagai jurusan di sebuah universiti awam di China telah memberikan ungkapan metafora melalui soalan tinjauan terbuka. Hasil analisis menunjukkan pelbagai pandangan positif dan negatif. Metafora positif seperti “peluang latihan,” “pemudah cara pembelajaran,” dan “bantuan diperibadikan” mencerminkan potensi AI dalam menyokong pembelajaran individu dan meningkatkan kemahiran bertutur. Sebaliknya, metafora negatif seperti “kompleks” dan “kebergantungan” menunjukkan kebimbangan terhadap penggunaan teknologi ini secara berlebihan. Dapatan ini penting untuk membantu pendidik dan perekabentuk kurikulum mengintegrasikan AI secara berkesan dalam pengajaran bahasa.